Effect of prebiotic alternative to antibiotics in ration on meat quality parameter and cooking properties of broiler meat - Marufa, TH; Shaon, GM; Islam, MS; Sarker, T; Islam, SS; Mondol, D; Moin, TM; Biswas , G (Meat Research, 2023)
The research was conducted to investigate the effect of prebiotic on nutritional composition and cooking properties of broiler meat. 120 Habbard classic broiler male chicks were divided at random into five dietary treatment groups, each with three replications of eight chicks. The dietary treatment included T1= None of prebiotic or antibiotic; T2= 50mgantibiotic/kg of diet; T3=0.5g of prebiotic/kg of diet; T4= 1g of prebiotic/kg of diet and T5= 2g of prebiotic/kg of diet during the entire period. The commercial name of this prebiotic is AGREMOS. The T5 treatment group recorded the highest length and diameter of the drumstick (129.95mm and 63.49mm), while the T2 and T1 dietary groups recorded the lowest length and diameter of the drumstick (129.07mm and 40.81mm, respectively). Prebiotic significantly (p<0.001) affects the diameter and length of various broiler body parts as well as their weight (aside from dressing and feathers), drip loss, cooking loss, and cooking yield. CP%, EE%, Ash% of drumsticks and DM%, moisture%, and CP% of breasts were significantly (p<0.001) affected by prebiotic. For drumsticks, the dietary group T5 had the highest CP% and EE% at 27.86 and 2.63, respectively, while T1 and T3 had the lowest values at 24.01 and 2.47. In terms of breast muscle, T5 had the highest CP% (27.86) and T1 had the lowest CP% (24.01). Prebiotic is an excellent substitute for antibiotics in broiler diet. When compared to the other treatments, it was discovered that treatment T5 (2g prebiotic) was superior for the diet of broilers.